Levi Strauss Copper Riveted Overalls
A 100% mechanical rodeo. It moves. It talks. Its figures are all hand-carved likenesses of famous rodeo people. And they're all dressed in authentic Western togs miniature replicas of garments made in California since 1853 by Levi Strauss & Company. Don't miss it... the hit of the Golden Gate International Exposition... located in Vacationland.